Really works what..................................
Answer:
1) 4x^(2)+11x+6 Factored--> (4x+3) (x+2)
2) 4x^(2)+10x+6 Factored--> (2x+3)(2x+2)
3) 4x^(2)+14x+6 Factored--> (x+3)(4x+2)
Step-by-step explanation:
Factor: 4x^(2)+11x+6 (<em>step by step)</em>
<em>1) Split the second term (11x) into two terms</em>
<em> </em>4x^2 + 8x + 3x + 6
<em>2)Factor out common terms in the first two terms, then in the last two terms.</em>
4x(x + 2) + 3(x + 2)
<em>3) Factor out the common term x + 2</em>
<em> </em> (x + 2) (4x + 3)
Repeat the above steps for similar questions!
Answer:
x= -2, y = -3
Step-by-step explanation:
1. substitute x = 4+2y in the first equation: 
simplify it : 
2. isolate y in 8 + 5y = -7 --> 5y = -7 - 8 -->
3. solve for y: 5y = -15 --> y = -15/5 --> y= -3
4. solve for x: x = 4 + 2y
x = 4 + 2(-3)
x = 4 + (-6)
x = -2